2011
DOI: 10.1161/circulationaha.110.971986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 Mitogen-Activated Protein Kinase Improves Nitric Oxide–Mediated Vasodilatation and Reduces Inflammation in Hypercholesterolemia

Abstract: Background-Oxidized low-density lipoprotein reduces endothelial nitric oxide production (an important mediator of vasoregulation) and activates p38 mitogen-activated protein kinase (MAPK), a mediator of vascular inflammation. Animal models of vascular stress have previously predicted improvements in vascular function after p38 MAPK inhibition. We hypothesized that a selective p38␣/␤ MAPK inhibitor (losmapimod; GW856553) would improve compromised nitric oxide-mediated vasoregulation in patients with hypercholes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 56 publications
(46 reference statements)
5
88
0
Order By: Relevance
“…p38 activity has been demonstrated to be important at various points in plaque maturation. 61 Zhao et al 62 showed that the formation of the foam cells in response to oxidized LDL depended on p38 activation. The oxidized LDL likely activates Toll-like receptors that lead to p38 activation, the degradation of extracellular matrix, and plaque instability.…”
Section: Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…p38 activity has been demonstrated to be important at various points in plaque maturation. 61 Zhao et al 62 showed that the formation of the foam cells in response to oxidized LDL depended on p38 activation. The oxidized LDL likely activates Toll-like receptors that lead to p38 activation, the degradation of extracellular matrix, and plaque instability.…”
Section: Atherosclerosismentioning
confidence: 99%
“…For example, as measured with use of a whole blood assay, p38 activity was decreased by an average of 45% at 3 hours, and 35% at 6 hours, after the last oral dose of an inhibitor with a half-life of Ϸ12 hours. 61 Furthermore, these values were obtained after 28 days of dosing, presumably at steady state. 61 In this particular trial, the inhibitor was administered twice per day suggesting p38 activity at trough, immediately before the next dose, would be Ϸ20%.…”
Section: Clinical Trials Of P38 Inhibition For Cardiovascular Indicatmentioning
confidence: 99%
See 1 more Smart Citation
“…45 p38 mapk activity has also been found to be increased in endothelial progenitor cells from patients with coronary artery disease, and inhibition of p38 mapk increases the number of endothelial progenitor cells from these patients. 46 Importantly, a recent clinical study demonstrated that p38 mapk inhibitor is able to improve endothelial function in hypercholesterolemic patients, 47 and reduces atherosclerotic lesion progression in ApoE-/-mice. 48 Enhanced p38 mapk activity has also been found in adipocytes from type II diabetic patients 49 and in the heart of high-fat diet-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK pathway is important in numerous cell processes, including myocyte apoptosis, hypertrophy and inflammation, which may contribute to progressive left ventricular remodeling post-MI and the transition to heart failure (14,15). Pharmacological inhibitors of p38 MAPK have been shown to decrease myocyte apoptosis and improve cardiac function and heart failure in vitro and in vivo (16,17).…”
Section: Introductionmentioning
confidence: 99%